Blended Learning: Engaging Students in the New Normal Era 15th International Conference, ICBL 2022, Hong Kong, China, July 19-22, 2022, Proceedings - Li, Richard Chen.; Cheung, Simon K. S.; Ng, Peter H. F.; Wong, Leung-Pun.; Wang, Fu Lee. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 15th International Conference on Blended Learning, ICBL 2022, held in Hong Kong, China, in August 2022. The 31 papers presented in this volume were carefully reviewed and selected from 80 submissions. The conference theme of ICBL 2022 is Blended Learning: Engaging Students in the New Era. The papers are organized in topical sections named: Game-based Learning and Augmented Learning Environment; Computer Supported Collaborative Learning; Enriching Learning Experience with Blended and Online Learning; Content Development and Practice for Blended Learning and Beyond.
Game-based Learning and Augmented Learning Environment -- Computer Supported Collaborative Learning -- Enriching Learning Experience with Blended and Online Learning -- Content Development and Practice for Blended Learning and Beyond.
Keywords: Education-Data processing; Application software; User interfaces (Computer systems).; Human-computer interaction; Social sciences-Data processing; Computers and Education; Computer and Information Systems Applications; User Interfaces and Human Computer Interaction; Computer Application in Social and Behavioral Sciences